Reacción de los indígenas de Cajamarca ente a la Independencia de Trujillo y Lima, 1821-1822 - Espinoza Soriano, Waldemar (2007)
The Creole population of the city of Cajamarca, capital of its namesake province, upon a suggestion and invitation of the marquis of Torre Tagle, Intendent of Trujillo, declared its independence on 8 January 1821. When the local indigenous nobles learnt this fact they argued that the new State should be ruled by a descendent of Atahualpa who lived in the neighbourhood. Their request was heard and transmitted to Torre Tagle but no answer was ever given to the Indian nobility. This proves that for the Creole oligarchy and aristocracy of the Intendence of Trujillo the descendants of the Incas never represented a ruling choice.